2021
DOI: 10.1371/journal.pone.0249952
|View full text |Cite
|
Sign up to set email alerts
|

Is concentration an indirect link between social anxiety and educational achievement in adolescents?

Abstract: Social anxiety is associated with reduced educational achievement. Given that concentration is a predictor of educational achievement, and social anxiety symptoms are associated with reduced concentration in class, this prospective study examined the possibility that social anxiety may impair educational achievement through reduced classroom concentration. A sample of 509 participants (53.8% female; M age: 12.77 years [SD = 0.81]) recruited from secondary schools completed questionnaires assessing social anxie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 49 publications
2
12
0
1
Order By: Relevance
“…This result further confirmed the adverse influence of social phobia on academic performance ( Baptista et al, 2012 ; Leigh et al, 2021 ; Vilaplana-Pérez et al, 2021 ; Archbell and Coplan, 2022 ) and on L2 acquisition and learning ( King, 2013a , b ). Meanwhile, the current research provided much empirical evidence and specifically elucidated how and to what extent social phobia could affect L2 WTC.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…This result further confirmed the adverse influence of social phobia on academic performance ( Baptista et al, 2012 ; Leigh et al, 2021 ; Vilaplana-Pérez et al, 2021 ; Archbell and Coplan, 2022 ) and on L2 acquisition and learning ( King, 2013a , b ). Meanwhile, the current research provided much empirical evidence and specifically elucidated how and to what extent social phobia could affect L2 WTC.…”
Section: Discussionsupporting
confidence: 73%
“…It was manifested that the female social phobics who participated in the study demonstrated significantly lower academic performances than those without social phobia. In the same vein, Leigh et al (2021) investigated the route from social anxiety to educational achievement via concentration. By analysing the results from a sample of 509 secondary school students in the United Kingdom, it was revealed that adolescents with social phobia generally had concentration problems, which might lead to unsatisfactory academic outcomes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…While on the other hand, the third hypothesis exclaimed that academic selfefficacy and social anxiety play a significant role in the prediction of academic success and it was put through a regression test whose analysis proved that it is justified. It showed that social anxiety significantly predicts the academic performance of Pakistani university students which again is supported by the existing literature that says that "social anxiety symptoms reduce the ability of the adolescent to concentrate in class which, in turn, impacts on their educational achievement over time, over and above baseline educational achievement and depression symptoms" (Leigh, 2021).…”
Section: Resultssupporting
confidence: 55%
“…In turn, unpleasant emotions in the school context have been associated with negative consequences, such as school burnout [ 29 ]. In other cases, an association has been found between social anxiety and low academic performance, with the possibility that the first could affect the second by limiting concentration in the classroom [ 30 ].…”
Section: Introductionmentioning
confidence: 99%